2017
DOI: 10.1002/ep.12639
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of sulfamethazine antibiotics in Fenton‐like system using Fe3O4 magnetic nanoparticles as catalyst

Abstract: In this study, Fe3O4 magnetic nanoparticles (MNPs) were synthesized, characterized and used for the degradation of sulfamethazine (SMT). The results showed that Fe3O4 MNPs were efficient and reusable heterogeneous catalytic for SMT degradation in a Fenton‐like system. More than 80% of the SMT was degraded under optimal conditions: initial pH of 3.0, 20 mM of H2O2, Fe3O4 MNPs dose of 1.0 g/L, and initial concentration of SMT 20 mg/L (initial total organic carbon: 10.4 mg/L). Among the parameters that affect SMT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…The performance of the catalysts in some other studies is shown in table 1 . Those catalytic materials generally need to be in a higher temperature (35–45°C) and a narrower pH (2–3.5) range in the catalytic degradation of sulfamethoxazole [ 65 , 69 , 70 ]. However, we found that the catalytic degradation efficiency of SMT (5 g l −1 ) by sch–FLG was around 100% at a lower temperature (28°C), and in a wide range of initial solution pH values (1–9).…”
Section: Resultsmentioning
confidence: 99%
“…The performance of the catalysts in some other studies is shown in table 1 . Those catalytic materials generally need to be in a higher temperature (35–45°C) and a narrower pH (2–3.5) range in the catalytic degradation of sulfamethoxazole [ 65 , 69 , 70 ]. However, we found that the catalytic degradation efficiency of SMT (5 g l −1 ) by sch–FLG was around 100% at a lower temperature (28°C), and in a wide range of initial solution pH values (1–9).…”
Section: Resultsmentioning
confidence: 99%
“…Decrease of catalytic activity in heterogeneous process is often reported in the literature and is mainly related to agglomeration of the catalyst and occupation of reactive sites with degradation products. 1,54 Catalyst CAT3 was used in further experiments to evaluate other degradation parameters such as H 2 O 2 concentration and pH.…”
Section: Effect Of Titanium Content On Degradation Of Ar8mentioning
confidence: 99%
“…Hydroxyl radicals, HO • , are powerful oxidants that are often used in water treatment to oxidize and degrade non‐biodegradable or persistent organic compounds. The classical homogeneous Fenton system (Fe 2+ /H 2 O 2 ) is the most efficient among various technologies for HO • production . However, this system has two drawbacks.…”
Section: Introductionmentioning
confidence: 99%